2020
DOI: 10.1177/1043454220958643
|View full text |Cite
|
Sign up to set email alerts
|

Transition From Hospital to Home Following Hematopoietic Stem Cell Transplantation: A Feasibility Study for “Rooming in”

Abstract: Background: The experience of hematopoietic stem cell transplant (HSCT) on both the patients and their caregivers is complex and challenging during hospitalization and post discharge. Complex patient populations require heightened attention on discharge practices to ensure that they are prepared for home regimens. “Rooming in” is a standardized intervention implemented prior to discharge that allows patients and caregivers to assume post discharge care with the support of staff. Other complex patient populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Frequent appointments, complex medication regimens, and infection prevention strategies are time-intensive aspects of everyday life 8,9 . Parents experience difficulty coping due to stress from the children's intense caregiving needs during HSCT recovery 10 . Parents prioritize children's needs over their own, often overlooking their own self-care 11 …”
mentioning
confidence: 99%
“…Frequent appointments, complex medication regimens, and infection prevention strategies are time-intensive aspects of everyday life 8,9 . Parents experience difficulty coping due to stress from the children's intense caregiving needs during HSCT recovery 10 . Parents prioritize children's needs over their own, often overlooking their own self-care 11 …”
mentioning
confidence: 99%
“…A printed booklet for educating patients was prepared after reviewing the literature [26,27,31,32]. The booklet was evaluated by 10 different professionals, namely two hematologists, four hematology nurses, and four nursing academicians.…”
Section: Interventionsmentioning
confidence: 99%
“…Lin et al [ 8 ] reported that a hospital-to-home transitional care program improved the self-efficacy and QoL of the stroke survivors, and reduced unplanned hospital readmissions during the 24-week follow-up. To date, only 1 study has explored the feasibility of a discharge intervention named “Rooming in” for caregivers of pediatric HSCT recipients, and they demonstrated that “Rooming in” could lower the coping difficulty scores of caregivers [ 9 ]. However, no study has focused on the effects of discharge planning on UCBT recipients; in addition, the impact of discharge planning on patients’ readmission rates, self-efficacy, QoL, and clinical outcomes are still uncertain.…”
Section: Introductionmentioning
confidence: 99%